Trends in post‐1950 riparian vegetation recovery in coastal catchments of NSW Australia: Implications for remote sensing analysis, forecasting and river management - Zhang, Nuosha; Fryirs, Kirstie (Earth surface processes and landforms, 2023)
Extensive riparian vegetation clearance occurred in many rivers of southeastern Australia throughout the 19th and 20th century, post colonisation. With improvements in river management practices, coincident with a period of minimal flooding, vegetation recovery of riparian corridors has been occurring since the 1980s in all coastal catchments of New South Wales (NSW). However, the catchment‐by‐catchment spatial pattern and temporal trends, trajectories and rates of vegetative recovery remain unknown. We reconstruct a 70‐year time series of change in riparian vegetation coverage for all rivers in coastal catchments of NSW, utilising historical aerial imagery, Landsat and Sentinel data and a manual digitisation and machine learning method. We quantify and statistically analyse decadal trends in woody and non‐woody vegetation coverage along 19 485 km of stream length in 20 catchments. Across the region, there has been, on average, a 40% increase in vegetation coverage along riparian corridors since the 1950s, with some catchments increasing towards a current day coverage of between 60% and 80%. However, the trends vary by subregion and by catchment. An early logarithmic increase occurred up to 2004 on the North coast, and a recent and accelerated exponential increase since 1995 has occurred on the South coast. After a steep initial increase, riparian corridor vegetation coverage has fluctuated on the Central coast since about 1995. We used these linear, exponential and logarithmic regressions to undertake preliminary forecasts of possible future timeframes of riparian vegetation change, based on several climate, management and natural disaster disturbance scenarios. If the current trend continues, riparian vegetation coverage can reach 70% across the region by 2055. However, if management practices change or catastrophic disturbance events such as fire and flood occur, increases in riparian vegetation coverage could be set back by up to 30 to 40 years.